Laser surface modification of boronickelized medium carbon steel. (November 2015) - Bartkowska, Aneta; Pertek, Aleksandra; Kulka, Michał; Klimek, Leszek
Abstract: A two-step process was applied to produce the multicomponent boride layers. Boronickelizing consisted of nickel plating and diffusion boriding. Two different methods of heat treatment of boronickelized C45 steel were used: a typical through-hardening, and a laser surface modification with remelting. Microstructure and some mechanical properties of these layers were examined. Microstructural characterization was studied using optical microscope, Scanning Electron Microscope, energy-dispersive X-ray microanalysis, Electron Back-Scatter Diffraction and X-ray diffraction. The laser modification improved wear resistance, cohesion as well as low-cycle fatigue of the boronickelized layer. Compressive stresses, occurring after laser remelting, could be the reason for the advantageous mechanical behavior of the layer. Highlights: Nickel plating and diffusion boriding were used to produce multicomponent layers. Two methods of heat treatment were used: typical hardening and laser remelting. The advantageous influence of LHT on mechanical properties was observed. LHT caused the occurrence of compressive stresses in the layer.